A Systematic Review of Gastrointestinal Manifestations in Children Presenting with COVID-19 - Salvatore, Silvia; Agosti, Massimo; Arrigo, Serena; Stracuzzi, Marta; Dilillo, Dario; Folgori, Laura; Giacchero, Roberta; Giacomet, Vania; Longoni, Emma; Meini, Antonella; Marseglia, Gian Luigi; Plebani, Alessandro; et al. (International Journal of Pediatrics and Child Health, 2021)
SARS-CoV-2 infection commonly presents with mild to severe respiratory symptoms and possibly other organs involvement. Gastrointestinal manifestations have been frequently documented in adult patients whilst their occurrence in children is uncertain. This study aimed to perform a Systematic Review of gastrointestinal symptoms in children with Coronavirus disease (COVID-19) and to compare these clinical findings with those reported in a cohort of Italian children in the early phase of pandemic. Methods: Literature search was conducted using the Cochrane Library and MEDLINE (via Pubmed) databases from 1st December 2019 to 28th April 2020, according to the PRISMA guidelines. The following search terms were inserted: “Coronavirus” OR “COVID-19” OR “SARS-CoV-2” AND “gastrointestinal” or “diarrhea”. Only papers including children (0-18 years) and gastrointestinal symptoms were considered as eligible. Data records of children living in Lombardy, Italy, with infection of SARS-CoV-2 diagnosed by rRT-PCR on pharyngeal swabs, from 1st March to 28th April were also collected, analyzed and compared. Results: The Systematic Review showed that only a minority of studies assessed gastrointestinal symptoms in children. However, diarrhea accounted for 0-50%, vomit 5-67% and abdominal pain 5.8-33.3% of infected children and gastrointestinal symptoms may represent the sole feature of COVID-19. Gastrointestinal symptoms were reported in 51/116 (44%) Italian children with SARS-CoV-2 infection. Poor feeding was present in 23.3% of children, diarrhea (median duration 2.3 days, range 1-5 days) in 22.4%, vomit in 10.4% and abdominal pain in 6.9% of cases. Respiratory symptoms were reported in 35.3% of children with gastrointestinal symptoms that represented the first clinical manifestation of COVID-19 in 25% of all patients. Conclusions: We found that gastrointestinal symptoms are common in children with COVID-19 and, in some cases, they may represent the first and the sole clinical manifestation of SARS-CoV-2 infection. Health care professionals must be aware of the frequent gastrointestinal involvement in children to assure an accurate diagnosis and therapeutic management. The correct identification of children with COVID-19 is also crucial to adopt preventive measures and to limit the transmission of the virus.